Integrated management system: The design portfolio management; Neftyanoe Khozyaistvo - Oil Industry; № 10 - Chetverikov V. V.; Gordievskikh V. V.; Galaktionov E. A.; Malishenko (Malyshenko) A. M. Alexanedr Maximovich; Voronin A. V.; Gromakov R. I.
Presented are the conception and three-fire structure of the design integrated management system for a designing organization. The level of design portfolio management is described in details. A special priority is given to the double-lined system of planning and executing of the design